MENINGKATKAN KETERAMPILAN MENULIS KARANGAN SEDERHANA MELALUI PENGGUNAAN MEDIA GAMBAR SERI - Hasmira Hasmira (Pedagogik Journal of Islamic Elementary School, 2018)
This research is to find out how to improve the skill of writing simple essay through the use of drawing media series in fourth grade students of Islamic Elementary School Datok Sulaiman  Palopo City. Research using qualitative and quantitative approach with Classroom Action Research (CAR) which is designed through two cycles. Research subjects, students of Islamic Elementary School Datok Sulaiman class IV that number 24 students. Data collection techniques used, namely observation, documentation, and tests. The research data obtained were analyzed by using descriptive statistic formula (percentage) to express descriptively the research result. Furthermore, to discuss and explain the results of research that is quantitative descriptive then used techniques of data reduction analysis, data presentation, and conclusion. The results of the study found that in prasiklus stage, the average score of students' writing skill is 54.37 with 20% classical learning completeness. After implemented the learning by applying Media drawing series, in the first cycle, the average score of students' simple writing skill is 56.25 with 50% complete classical learning. Furthermore, the cycle IIdengan average value of simple writing skill is 76.45 with 66% complete classical learning. Thus, the skill of writing a simple essay in the fourth grade of Islamic Elementary School Datok Sulaiman Palopo by applying the series image media conducted from the first cycle to the 2 show significant results. Thus, serial image media need to be referenced by teachers in activities.